Comparative Impact of Black Coffee and Milk Coffee on Prediabetes in Obese Adults - Eka Febriyanti; Huwainan Nisa Nasution; Fardella Lufiana (Jurnal Kesehatan Masyarakat, 2026)
Obesity is a major risk factor for metabolic diseases such as diabetes mellitus, hypertension, and cardiovascular disorders, primarily through the mechanism of insulin resistance. One contributing factor to obesity is the increasing consumption of sugar sweetened beverages, including milk coffee. However, coffee also contains bioactive compounds with potential protective effects. This study aimed to compare the effects of pure black coffee and milk coffee consumption on prediabetes status and fat mass among obese individuals. An analytical observational study with a cross sectional design was conducted in Medan City from December 2024 to February 2025 involving 82 obese participants aged 19–45 years. Coffee intake was assessed using a Food Frequency Questionnaire (FFQ), fasting blood glucose levels were measured using spectrophotometry, and fat mass was evaluated with a Body Composition Analyzer. Data were analyzed using a chi-square test with a significance level of p < 0.05. Results showed no significant difference in prediabetes incidence between black coffee and milk coffee consumers (p = 0.925). Similarly, fat mass did not differ significantly between groups (31.1 ± 7.4 vs. 31.7 ± 7.3). In conclusion, consumption of black coffee or coffee with milk showed no significant effect on prediabetes incidence or fat mass among obese individuals.